Re-writing international relations - Çapan, Zeynep Gülşah. (Lanham, Maryland)
viii, 119 sayfa
Keywords: This book tells a different story of International Relations by challenging disciplinary and theoretical boundaries from the Turkish perspective with the aim of creating a more connected and global International relations.